Oḍiśāra bikāśare patra- patrikāra prabhāba : Oḍiā patra-patrikāra pañji saṃyojita - Misra, Gopal Chandra, 1925- (Ya. Miśra : paribeshaka, Granthamandira, 1979)
Study on the influence of Oriya periodicals on the sociopolitical development in Orissa.